2020
DOI: 10.1021/acsami.9b21576
|View full text |Cite
|
Sign up to set email alerts
|

Far-Red Carbon Dots as Efficient Light-Harvesting Agents for Enhanced Photosynthesis

Abstract: Sunlight utilization by plants via the photosynthesis process is limited to the visible spectral range. How to expand the utilization spectral range via construction of a hybrid photosynthetic system is a hot topic in this field. In this work, far-red carbon dots (FR-CDs) with excellent water solubility, good biocompatibility, high quantum yield (QY), and superior stability were prepared by a one-step microwave synthesis in 3 min. The as-prepared FR-CDs is an efficient converter transferring ultraviolet A (UV-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
95
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(101 citation statements)
references
References 61 publications
3
95
0
Order By: Relevance
“…The maximum absorption of the reaction center in PSI and PSII is about 700 and 680 nm (denoted as P700 and P680), respectively, to drive photosynthesis. The synergistic effect of P680 and P700 was discovered by Emerson that photosynthetic efficiency enhancement will occur simultaneously driven [3] . Various strategies have been developed to improve the photosynthetic rate of plants.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The maximum absorption of the reaction center in PSI and PSII is about 700 and 680 nm (denoted as P700 and P680), respectively, to drive photosynthesis. The synergistic effect of P680 and P700 was discovered by Emerson that photosynthetic efficiency enhancement will occur simultaneously driven [3] . Various strategies have been developed to improve the photosynthetic rate of plants.…”
Section: Figurementioning
confidence: 99%
“…The synergistic effect of P680 and P700 was discovered by Emerson that photosynthetic efficiency enhancement will occur simultaneously driven. [3] Various strat-egies have been developed to improve the photosynthetic rate of plants.…”
mentioning
confidence: 99%
“…This is the first report on employing the unique dual‐emission trait to augment plant photosynthesis. In 2020, this research team prepared far‐red CDs that can convert ultraviolet light into far‐red emission [57] (Figures 7a, 7b) and NaYF 4 :Yb,Er@CDs nanocomposites that can convert NIR irradiation into red light (Figures 7c, 7d) [58] …”
Section: Interaction Between Cds and Plantsmentioning
confidence: 99%
“…In addition, the chemical surface properties of CDs can be adjusted by doping various heteroatoms, such as N, F, B, S and Mg to improve their performance. [19][20][21][22][23] It has been demonstrated that the CDs attached to the composites can not only increase the ion transport interface between the electrode and electrolyte, but also improve the conductivity of the composite material through edge effect and quantum constraint, effectively improving the specic capacitance and specic capacity, as well as cycling stability. 24,25 For example, Hou et al synthesized carbon quantum dots (CQDs) and their derivative 3D porous carbon frameworks and applied them to sodium ion batteries, which had a long cycle life and excellent multiplier performance.…”
Section: Introductionmentioning
confidence: 99%